Infant and Young Child Feeding Policy assessment in Thailand with World Breastfeeding Trends Initiative - Cetthkrikul, Nisachol; Topothai, Chompoonut; Sasiwatpaisit, Nonglapat; Tupsart, Kitiporn; Hangchawanich, Yuppayong (Journal of Health Science of Thailand, 2017)
World Breastfeeding Trends Initiative (WBTi) is an international standard tool used for assessing the progress of policy implementation of Infant and Young Child Feeding Policy (IYCF) recommended by World Health Organization. Thai Breastfeeding Center Foundation and Department of Health, Ministry of Public Health introduced the use of the WBTi to assess the breastfeeding situation of Thailand in 2010; and the result showed fair performance at that time. However, during the last 5 years, many measures and regulations were implemented by related stakeholders to support, promote, and protect the breastfeeding. The objective of this study was to re-assess the situations and gaps of breastfeeding in Thailand using WBTi in order to provide policy recommendation to policy makers. This study was conducted in 2015 as a cross-sectional study collecting data from stakeholders using group interviews. The results showed that Thailand’s total score was 84.5 which means we have done “fair” or moderate level in implementing the Global Strategy for Infant and Young Child Feeding practice. However, overall situation was better than 2010 as higher score was observed (84.5 for 2015 compare to 75.5 in 2010). The key gaps were identified which included absence of comprehensive national policy or strategic plan of IYCF, ineffective enforcement of existing measures and regulations and inadequate information sharing and public commu-nication on IYCF practices for mothers and families. The study came up with 3 short-term recommenda-tions including (1) establishing the comprehensive national IYCF policy and strategic plan, (2) legislating the International Code of Marketing of Breast-milk Substitutes into national law and (3) increasing communication channels to the general public in order to provide correct information, and to create under-standing and appropriate social norms about IYCF practices.